2016
DOI: 10.1177/0266666915596804
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to engage in word-of-mouth behavior on social network sites

Abstract: The main objective of this study was to enhance the understanding of users' motivation to engage in word-ofmouth behavior on social network sites. This study conducted a hierarchical regression analysis to examine the motivations of social and personal constructs that may influence users' engagement in word-of-mouth. The results posited that not only social constructs (tie strength, expressiveness, social enhancement, relationship management, normative influence, and informational influence), but also personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 69 publications
2
20
0
18
Order By: Relevance
“…The result of this study similar to the previous study that revealed informational influence as one of the factors that influence people to engage in WOM (Luarn et al, 2016). The customer has the motivation to affect others by providing some information regarding the product or service.…”
Section: Effect Of Customer Satisfaction As Mediation Variable Betweesupporting
confidence: 86%
“…The result of this study similar to the previous study that revealed informational influence as one of the factors that influence people to engage in WOM (Luarn et al, 2016). The customer has the motivation to affect others by providing some information regarding the product or service.…”
Section: Effect Of Customer Satisfaction As Mediation Variable Betweesupporting
confidence: 86%
“…Anderson mendefinisikan word-of-mouth sebagai komunikasi informal antara pihak yang dekat tentang bagaimana penilaian mereka mengenai barang dan jasa tertentu (Ring, Tkaczynski, & Dolnicar, 2014). Sementara Bristor menjelaskan bahwa word-of-mouth adalah suatu bentuk komunikasi interpersonal yang melibatkan informasi nonkomersil tentang suatu produk, jasa atau sebuah merk (Larceneux, 2013 (Luarn, Huang, Chiu, & Chen, 2016). recruited artists and added full-song streaming and music videos.…”
Section: Word-of-mouth Dan Internet Buzzerunclassified
“…In the literature, several studies aimed to find the significant factors affecting customer engagement in brand communities (Jayasingh and Venkatesh, 2015;Carlson et al, 2017;Guo et al, 2017). They focused on various factor types including social factors such as tie strength, trust, social identity, trust and reciprocity (Chahal et al, 2017;Kang et al, 2016;Carlson et al 2017;Tsai et al, 2017;Bohari, 2016), content based factors such as perceived usefulness and perceived enjoyment (Guo et al, 2017;Carlson et al, 2017;Dessart et al, 2015;Chahal et al, 2017), brand related factors such as satisfaction ore brand image (Dessart et al, 2015;Carlson et al, 2017) and customer related factors such as self image enhancement and altruism (Simon et al, 2016;Jahn et al, 2012;Luarn et al, 2016;Marbach et al, 2016). Heinonen (2017) focused on the effect customer based factors on behavioral, emotional and cognitive dimensions of customer engagement.…”
Section: Th Iadis International Conference Information Systems 2019mentioning
confidence: 99%
“…Various social factors have been proposed as drivers of customer engagement (Simon et al, 2016;de Castro, 2017;Luarn et al, 2016;Carlson et al, 2017;Chahal et al, 2017;Huang et al, 2013). Also, Jahn et al (2012) suggested that one most prominent needs of customers is related to content-oriented area which is based on functional and hedonic values.…”
Section: Antecedents Of Customer Engagementmentioning
confidence: 99%
See 1 more Smart Citation